SUMOylation and phosphorylation cross-talk in hepatocellular carcinoma - Tomasi, Maria Lauda; Ramani, Komal (Translational Gastroenterology and Hepatology, 2018)
Hepatocellular carcinoma (HCC) is a primary malignancy of the liver and occurs predominantly in patients with underlying chronic liver disease and cirrhosis. The large spectrum of protein post-translational modification (PTM) includes numerous critical signaling events that occur during neoplastic transformation. PTMs occur to nearly all proteins and increase the functional diversity of proteins. We have reviewed the role of two major PTMs, SUMOylation and phosphorylation, in the altered signaling of key players in HCC. SUMOylation is a PTM that involves addition of a small ubiquitin-like modifiers (SUMO) group to proteins. It is known to regulate protein stability, protein-protein interactions, trafficking and transcriptional activity. The major pathways that are regulated by SUMOylation and may influence HCC are regulation of transcription, cell growth pathways associated with B-cell lymphoma 2 (Bcl-2) and methionine adenosyltransferases (MAT), oxidative stress pathways [nuclear erythroid 2-related factor 2 (Nrf2)], tumor suppressor pathways (p53), hypoxia-inducible signaling [hypoxia-inducible factor-1 (HIF-1)], glucose and lipid metabolism, nuclear factor kappa B (NF-κB) and β-Catenin signaling. Phosphorylation is an extensively studied PTM in HCC. The mitogen-activated protein kinase (MAPK), phosphatidyl inositol/AK-strain transforming (PI3K/AKT), and C-SRC pathways have been extensively studied for deregulation of kinases and alteration in signaling of targets through phosphorylation of their substrates. Cross-talk between phosphorylation and SUMOylation is known to influence transcriptional activity of proteins and protein-protein interactions. In HCC, several SUMOylation-dependent phosphorylation events have been studied such as MAPK activation and c-SRC activity that have been reviewed in this work. The drastic effects of site-specific phosphorylation or SUMOylation on enzyme activity of signaling players and its effect on growth and tumorigenesis suggests that these PTMs are novel targets for therapeutic intervention in HCC.